Raw ready‐to‐eat seafood safety: microbiological quality of the various seafood species available in fishery, hyper and online markets. (4th December 2016) - Kim, H.W.; Hong, Y.J.; Jo, J.I.; Ha, S.D.; Kim, S.H.; Lee, H.J.; Rhee, M.S.
Abstract: Microbiological quality of 206 raw ready‐to‐eat seafood samples was investigated according to species (gizzard shad, halibut, rockfish, tuna, oyster and squid) and distribution channels (fishery, hyper and online market). Enumeration of aerobic plate count and total coliforms (TC) and pathogenic bacteria ( Bacillus cereus, Staphylococcus aureus and Vibrio parahaemolyticus ) was performed, and level of microbiological quality was classified into four groups: satisfactory, acceptable, unsatisfactory and unacceptable. Qualitative analysis was also performed for Escherichia coli and eight foodborne pathogens ( B. cereus, E. coli O157:H7, Listeria monocytogenes, Salmonella spp., S. aureus, Vibrio cholerae, V. parahaemolyticus, and Vibrio vulnificus ). Raw ready‐to‐eat seafood products revealed 0·5% at an unsatisfactory level and 4·9% at an unacceptable level due to ≥4 log CFU g −1 of TC in squid and ≥3 log CFU g −1 of V. parahaemolyticus in gizzard shad respectively. Gizzard shad was shown to be potentially hazardous, as its sashimi is eaten with its skin attached. Bacillus cereus, E. coli, S. aureus, V. parahaemolyticus and V. vulnificus were qualitatively detected. Samples from the fishery market showed higher detection rate especially in V. parahaemolyticus (21·6%) and V. vulnificus (1·7%) which indicates the need to improve microbiological safety of raw ready‐to‐eat seafood products in fishery market. Significance and Impact of the Study: Raw ready‐to‐eat seafood products like sashimi can be easily contaminated with various bacteria from aquatic environments and human reservoirs, which subsequently bring about a risk in food poisoning due to no heating process before consumption. The results of this study provide comprehensive microbiological data on various species of raw ready‐to‐eat seafood from various distribution channels. It may contribute to establish reasonable standard and effective strategies to ensure a good microbiological quality of raw ready‐to‐eat seafood for the safety of meals, like sashimi and sushi . Abstract : Significance and Impact of the Study: Raw ready‐to‐eat seafood products like sashimi can be easily contaminated with various bacteria from aquatic environments and human reservoirs, which subsequently bring about a risk in food poisoning due to no heating process before consumption. The results of this study provide comprehensive microbiological data on various species of raw ready‐to‐eat seafood from various distribution channels. It may contribute to establish reasonable standard and effective strategies to ensure a good microbiological quality of raw ready‐to‐eat seafood for the safety of meals, like sashimi and sushi .